Research methods in education and psychology integrating diversity with quantitative & qualitative approaches - Mertens, Donna M. (Sage, 1998)
Focused on providing as full a picture as possible of what is considered to be "good" research, Research Methods in Education and Psychology explains quantitative and qualitative methods and incorporates the viewpoints of various research paradigms into the descriptions of these methods. It not only covers two of the standard paradigms (postpositivist and interpretive/constructivist) but discusses a relative newcomerthe emancipatory paradigm - that is inclusive of the perspectives of feminists, ethnic/racial minorities, and persons with disabilities. In each chapter, Donna M. Mertens carefully explains a step of the research process from the literature review to types of research method to analysis and reporting of quantitative or qualitative approaches. As an added plus, she includes a sample study and abstract in each chapter to illustrate the concepts discussed in that chapter.